The perception of stakeholders on corporate social responsibility: The case study of PKT Logistics Group Sdn Bhd - Hemalatha, Selvarathunam (2015)
Today, Corporate Social Responsibility (CSR) over the couple of years expands its consciousness in the public as a complete motivating stakeholder‟s element and achieved eminence on the corporate strategic schema. Therefore, an intricate confront for companies is to build a business deliberate for CSR, protecting the fresh investments through affirmative benefits to the company. Between, numerous firms nowadays view CSR as a secluded pricey activity which separated from core business. The fundamental of this master thesis is to explore the perceptions of stakeholders (shareholder, employee and customer) on CSR in logistic industry at Malaysia. The researcher has outlined PKT Logistics Group Sdn Bhd- Malaysia (PKT) firm in order to investigate about this issue. The principle objective of this research is determine stakeholders‟ perception towards CSR influencing the firm as well as developing new CSR model according to stakeholders‟ perception and expectation. The data was collected from stakeholders of PKT via interview section. Overall this study discovers the linkages between Stakeholder, CSR and Business Ethics and Competitive Advantage. These studies present groundwork for future research and recognize numerous vital suggestions for the corporate leaders to deem in terms of CSR venture within their business portfolio